Development Of Project-Based Teaching Modules To Improve Students' Spatial Thinking Skills In Geography Learning - Endang Sutiah; Sunarty Suli Eraku; Nurfaika (International Journal of Technology and Education Research, 2025)
This study aims to develop, validate, and evaluate the practicality and effectiveness of a Geography teaching module based on Project-Based Learning (PjBL) for Remote Sensing material to enhance students' spatial thinking skills at SMAN 4 Gorontalo. The research employed a Research and Development (R&D) design using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. Research subjects included students from classes X.7 and X.8, as well as Geography teachers from seven public senior high schools in Gorontalo City. Expert validation results indicate that the module is "highly feasible," receiving an average feasibility score of 94% from module experts and 91% from material experts. The practicality level is classified as very good based on classroom observations of teacher activity (97%) and student responses (92%). The module's effectiveness is demonstrated by significant improvements in learning outcomes, with N-Gain scores of 0.68 for class X.7 and 0.69 for class X.8—both categorized as moderate improvement. These findings reveal that the PjBL-based module successfully enhances spatial thinking skills, increases student engagement, and effectively supports the implementation of the Merdeka Curriculum. The module is recommended as an applicable and contextual learning resource for Geography teachers.